2012
DOI: 10.1111/ane.12001
|View full text |Cite
|
Sign up to set email alerts
|

Perampanel Study 207: long-term open-label evaluation in patients with epilepsy

Abstract: Objectives -Evaluate interim long-term tolerability, safety and efficacy of adjunctive perampanel, a novel a-amino-3-hydroxy-5-methyl-5-isoxazolepropionic acid (AMPA)-receptor antagonist, in patients with refractory partial-onset seizures. Materials and methods -Study 207, an open-label extension (OLE) study (ClinicalTrials.gov identifier: NCT00368472), enrolled patients (18-70 years) who completed one of two randomized, placebocontrolled, dose-escalation Phase II studies. The OLE Treatment Phase comprised a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 14 publications
(31 reference statements)
11
63
1
2
Order By: Relevance
“…Low-dose margins of efficacy over motor effects have been reported before in rodents (Hanada et al, 2011). Although it is well tolerated, perampanel has shown motor impairments in human studies and in phase III data Krauss et al, 2012Krauss et al, , 2013Rektor et al, 2012). Thus, although protective indices in rodents are not always fully translatable into human motor side-effect liabilities (Löscher and Nolting, 1991), the data with perampanel in the current study and in Hanada et al (2011) have uncovered the dose-dependent motor consequences of perampanel in humans.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Low-dose margins of efficacy over motor effects have been reported before in rodents (Hanada et al, 2011). Although it is well tolerated, perampanel has shown motor impairments in human studies and in phase III data Krauss et al, 2012Krauss et al, , 2013Rektor et al, 2012). Thus, although protective indices in rodents are not always fully translatable into human motor side-effect liabilities (Löscher and Nolting, 1991), the data with perampanel in the current study and in Hanada et al (2011) have uncovered the dose-dependent motor consequences of perampanel in humans.…”
Section: Discussionsupporting
confidence: 51%
“…Given the motor impairments observed in rodents (Hanada et al, 2011;Rogawski and Hanada, 2013; present study) and the ataxia and dizziness reported in epileptic patients at higher doses of perampanel Krauss et al, 2012Krauss et al, , 2013Rektor et al, 2012), it is suggested that cerebellar AMPA receptor blockade is a primary mediator of the main side effects of perampanel. Our results showing that both rodent and human cerebellar AMPA receptors are equally inhibited by perampanel further corroborate this hypothesis.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, treatment was associated with an acceptable and consistent safety profile. Two long-term extension trials were also carried out to investigate the long-term efficacy and safety of perampanel [42,43], and interim analyses have so far shown consistent results with the Phase III trials.…”
Section: Phase II and Phase Iiimentioning
confidence: 99%
“…Перампа-нел -мощный высокоселективный неконкурентный ингибитор ионотропных AMPA-рецепторов постсинап-тических мембран нейронов на уровне неокортекса и гиппокампа [6,9,26,41]. По мнению многих авторов, перампанел -первый АЭП со специфическим дейст-вием на обмен глутамата (опосредованное глутаматом возбуждение в ЦНС), эффективность и переносимость которого при резистентных фокальных приступах были доказаны в клинических исследованиях III фазы [13, 17-21, 27, 28, 31].…”
unclassified